High Energy and Power Density Peptidoglycan Muscles through Super‐Viscous Nanoconfined Water - Haozhen Wang; Zhi‐Lun Liu; Jianpei Lao; Sheng Zhang; Rinat Abzalimov; Tong Wang; Xi Chen (Advanced Science, 2022)
Abstract Water‐responsive (WR) materials that reversibly deform in response to humidity changes show great potential for developing muscle‐like actuators for miniature and biomimetic robotics. Here, it is presented that Bacillus (B.) subtilis’ peptidoglycan (PG) exhibits WR actuation energy and power densities reaching 72.6 MJ m−3 and 9.1 MW m−3, respectively, orders of magnitude higher than those of frequently used actuators, such as piezoelectric actuators and dielectric elastomers. PG can deform as much as 27.2% within 110 ms, and its actuation pressure reaches ≈354.6 MPa. Surprisingly, PG exhibits an energy conversion efficiency of ≈66.8%, which can be attributed to its super‐viscous nanoconfined water that efficiently translates the movement of water molecules to PG's mechanical deformation. Using PG, WR composites that can be integrated into a range of engineering structures are developed, including a robotic gripper and linear actuators, which illustrate the possibilities of using PG as building blocks for high‐efficiency WR actuators.